PENGUATAN KEPEMIMPINAN SISWA MELALUI PROGRAM BELA NEGARA GUNA MENUMBUHKAN NILAI CINTA TANAH AIR (STUDI KASUS SMPN 12 BANDUNG) - Lex Divina, Yusticia; Budimansyah, Dasim; Sopianingsih, Pitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the contribution of the National Defense Program in strengthening student leadership to foster a sense of patriotism at SMPN 12 Bandung. The study employs a qualitative approach using a case study design. Participants included the vic1e principal, Civic Education teachers, military advisors, and seventh-grade students selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and document analysis, and were analyzed using thematic analysis. The results indicate that the program contributes to fostering patriotism through structured character development. Student leadership is primarily shaped through collective emotional experiences. However, critical dynamics were identified, including pseudo-compliance and a gap between actions and awareness (the civic knowledge–action paradox), where student discipline remains dependent on external control. This study confirms that the internalization of civic values is not linear but is influenced by social relations, context, and individual reflection.